Effects of diet and age on oxidative damage products in healthy subjects - Krajčovičová-Kudláčková, M; Valachovičová, M; Pauková, V; Dušinská, M (Physiological research, 2008)
Damage of molecules as a consequence of oxidative stress has been implicated in the pathogenesis of chronic diseases related to aging. Diet is a key environmental factor affecting the incidence of many chronic diseases. Antioxidant substances in diet enhance the DNA, lipid and protein protection by increasing the scavenging of free radicals. Products of oxidative damage of DNA (DNA strand breaks with oxidized purines or oxidized pyrimidines), lipids (conjugated dienes of fatty acids) and proteins (carbonyls) in relation to nutrition (vegetarian diet vs. non-vegetarian, traditional mixed diet) were measured in young women aged 20-30 years (46 vegetarians, 48 non-vegetarians) vs. older women aged 60-70 years (33 vegetarians, 34 non-vegetarians). In young subjects, no differences in values of oxidative damage as well as plasma values of antioxidative vitamins (C,beta-carotene) were observed between vegetarian and non-vegetarian groups. In older vegetarian group significantly reduced values of DNA breaks with oxidized purines, DNA breaks with oxidized pyrimidines and lipid peroxidation and on the other hand, significantly increased plasma values of vitamin C and beta-carotene were found compared to the respective non-vegetarian group. Significant age dependences of measured parameters (increase in all oxidative damage products and decrease in plasma vitamin concentrations in older women) were noted only in non-vegetarians. Vegetarian values of older women vs. young women were similar or non-significantly changed. The results suggest that increase of oxidative damage in aging may be prevented by vegetarian nutrition.
Keywords: Aging; antioxidancia; mužské pohlaví; oxidační stres; Male; senioři; Chromatography, High Pressure Liquid; Nutritional Physiological Phenomena; Female; Humans; metabolismus lipidů; Oxidative Stress; Lipid Metabolism; lidé; Antioxidants; Middle Aged; ženské pohlaví; lidé středního věku; poškození DNA; proteiny; vysokoúčinná kapalinová chromatografie; DNA Damage; Vitamins; stárnutí; vitaminy; dospělí; Diet, Vegetarian; Proteins; Adult; fyziologie výživy; dieta vegetariánská; Aged